78.1k views
5 votes
6x+2y=-18 it says determine how to rewrite in the form of ax + by= c where a B and C are consistent so that the sum of the new equation and be unchanged equation from the original system results in an equation of one variable

1 Answer

6 votes

You have the following system of equations:


\begin{gathered} -3x+4y=24 \\ 6x+2y=-18 \end{gathered}

To obain an equation with only one variable, from the previous system, you can multiply the first equation by 2, and then sum the result to the second equation, just as follow;

(-3x + 4y = 24)(2)

-6x + 8y = 48

next, sum the previous result to the second equation:

-6x + 8y = 48

6x + 2y = -18

10y = -66

Then, it is only necessary to multiply by 2 the first equation.

User Vprajan
by
5.2k points